Dealuminated ZSM-5 zeolite catalyst for ethylene oligomerization to liquid fuels - Saidina Amin, Nor Aishah (Science Press, 2002)
Ethylene oligomerization using ZSM-5 zeolite was investigated to study the role of Bronsted acid sites in the formation of higher hydrocarbons. The oligomerization of olefins, dependent on the acidity of ZSM-5 zeolite, is an important step in the conversion of natural gas to liquid fuels. The framework Si/Al ratio reflects the number of potential acid sites and the acid strength of the ZSM-5 catalyst. ZSM-5 with the mole ratio SiO2/Al2O3 equal to 30 was dealuminated for different periods of time according to the acidic ion-exchange method to produce ZSM-5 with various Si/Al ratios. The FT-IR analysis revealed that the integrated framework aluminum band, non-framework aluminum band, and silanol groups areas of the ZSM-5 zeolites decreased after being dealuminated. The performance of dealuminated zeolite was tested for ethylene oligomerization. The result demonstrated that the dealumination of ZSM-5 led to higher ethylene conversion, but the gasoline selectivity was reduced compared to the performance of a ZSM-5 zeolite. The characterization results revealed that the amount of aluminum in the zeolitic framework, the crystallinity of the ZSM-5 zeolite and the Si/Al ratio affected the formation of Bronsted acid sites. The number of the Bronsted acid sites on the catalyst active sites is important in the olefin conversion to liquid hydrocarbons.